Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s10530-016-1161-y
|View full text |Cite
|
Sign up to set email alerts
|

Invasive North American bullfrogs transmit lethal fungus Batrachochytrium dendrobatidis infections to native amphibian host species

Abstract: Invasive species can be a threat to native species in several ways, including 8 transmitting lethal infections caused by the parasites they carry. However, invasive species 9 may also be plagued by novel and lethal infections they acquire when invading, making 10 inferences regarding the ability of an invasive host to vector disease difficult from field 11 observations of infection and disease. This is the case for the pathogenic fungus 12 Batrachochytrium dendrobatidis (Bd) in Europe and one invasive host spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 53 publications
0
35
0
Order By: Relevance
“…Thus, infection risk for newts is not only a function of total zoospores to which newts are exposed (Experiment 2) but also how frequently newts are exposed to zoospores over time (Experiment 1). By extension, continuous and prolonged exposure would be most likely to manifest as increased mortality, and in support of this, a recent study showed how exposing newts constantly to an infected reservoir generated significant mortality (Miaud et al., ).…”
Section: Discussionmentioning
confidence: 85%
“…Thus, infection risk for newts is not only a function of total zoospores to which newts are exposed (Experiment 2) but also how frequently newts are exposed to zoospores over time (Experiment 1). By extension, continuous and prolonged exposure would be most likely to manifest as increased mortality, and in support of this, a recent study showed how exposing newts constantly to an infected reservoir generated significant mortality (Miaud et al., ).…”
Section: Discussionmentioning
confidence: 85%
“…boylii indicates that Bd prevalence and loads are highest in R. catesbeiana (American bullfrog) and H. regilla (Figure ). Both R. catesbeiana and H. regilla are considered to be vectors of Bd in California (Adams et al., ; Padgett‐Flohr & Hopkins, ; Reeder et al., ), and as an often‐tolerant Bd reservoir host, bullfrogs have been implicated in declines of amphibians in places throughout the world where they are not native, including California (Daszak et al., ; Jennings & Hayes, ; Miaud et al., ). H. regilla and R. catesbeiana may have provided sufficient reservoir hosts to allow for Bd persistence in the system, facilitating chytridiomycosis‐induced extinction of R .…”
Section: Discussionmentioning
confidence: 99%
“…Data were arranged prior to mapping so that Bd-positive samples would be superimposed on Bd-negative samples when they overlapped. Data include sampled specimens collected from Ventura, Santa Barbara, Los Angeles, and San Luis Obispo counties including California(Daszak et al, 2004;Jennings & Hayes, 1994a;Miaud et al, 2016). H. regilla and R. catesbeiana may have provided sufficient reservoir hosts to allow for Bd persistence in the system, facilitating chytridiomycosis-induced extinction of R. boylii.…”
mentioning
confidence: 99%
“…Bullfrogs are native to eastern North America (Bury and Whelan 1984), but now occur in nearly all lower 48 states and in over 40 countries. Their large size, high mobility, generalist eating habits, high fecundity, and function as a disease vector to other amphibians make the bullfrog an extremely successful invader and a major threat to biodiversity (Adams and Pearl 2007;Miaud et al 2016). For these reasons, evaluating sources, genetic properties and historical invasion pathways are key to the development of effective policy and management strategies needed to minimize their ecological impacts.…”
Section: Introductionmentioning
confidence: 99%